Analysis of similarity and dissimilarity of combining ability and heterosis for melon (Cucumis melo) fruit characters using multi-environments - HELFI EKA SAPUTRA; MUHAMAD SYUKUR; WILLY BAYUARDI SUWARNO; SOBIR SOBIR (Society for Indonesian Biodiversity, 2025)
Abstract. Saputra HE, Syukur M, Suwarno WB, Sobir. 2025. Analysis of similarity and dissimilarity of combining ability and heterosis for melon (Cucumis melo) fruit characters using multi-environments. Biodiversitas 26: 1870-1880. Evaluating combining ability and heterosis simultaneously across different environments facilitates the identification of hybrids with comparative advantages for melon breeding. Therefore, this study aimed to evaluate the consistency of General Combining Ability (GCA), Specific Combining Ability (SCA), heterosis, and heterobeltiosis on the characteristics of melon fruit in three environments, namely Bengkulu, Cilegon, and Argamakmur. The method used a completely randomized block design with one factor for each environment. The full diallel population (30 F1+6 parents) was repeated thrice, leading to 108 experimental units in each environment. The results showed that the best combined GCA value was followed by the optimal GCA value in each environment, despite genetic × environment and GCA × environment interaction. The consistency of GCA was due to the additive effect role that was not influenced by the environment. The best combined SCA value was not followed by the optimal SCA value in each environment, showing inconsistency due to non-additive effect roles (dominance and epistasis), which were easily influenced by the environment. The results also showed that genetic distance affected the values of heterosis and heterobeltiosis. Furthermore, crossbreeding between melon groups produced better heterosis and heterobeltiosis values than crossbreeding within the same group. Combining ability (GCA and SCA), mid-parent value, heterosis, and heterobeltiosis across multiple environments helped identify hybrids with comparative advantages for melon breeding.